The Apulian Spring, Twenty Years Later - Di Palma, Gabriele (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
The Apulian Spring has meant for a region of the South of Italy the attempt to reach an autonomous path to development. Twenty years later, is it possible to evaluate the main regional policies and the distributional effects on the population? The study aims to contribute to the debate on populism. According to the planning documents, Apulian Spring tried to transform economic and political regional institutions, making them more inclusive. Discussing the transformation of one of the least developed European regions in an attractive place can help understand the effects of progressive policies, in the age of right-wing populism.